Idiopathic facial pain - Орос, М. М. (Actual Dentistry, 2019)
Summary. Idiopathic facial pain is now regarded as a polyetiological syndrome, including myogenic or iatrogenic source of peripheral sensitization in the face, insufficiency of central pain management systems, and the presence of comorbid emotionally-affective disorders. Among patients with chronic pain, idiopathic facial pain accounts for 5.8 % of cases and was among the three most common causes of chronic prosopalgia. Pharmacotherapy is now more empirical, since controlled studies of the efficacy of drugs have not been conducted, antidepressants: phenelzine and doitiepin, which showed a moderate effect in the treatment of PIBO, are not currently available. Clinical experience shows that tricyclic antidepressants have the best effect. With exacerbation of pain, especially in the presence of a muscle component, some non-steroidal anti-inflammatory drugs, ketorolac and naproxen, have shown effectiveness. In particular, intranasal catrolac (Asprix) has shown high analgesic efficacy in our practice. Key words: face pain, neuralgia, antidepressants, ketorolac.